Analisis Nilai Religius dan Nilai Pendidikan Karakter pada Novel Sehidup Sesurga denganmu Karya Asma Nadia sebagai Bahan Ajar Bahasa dan Sastra Indonesia di SMA - Trisnawati, Trisnawati; Fauziah, Nurul (Universitas Mathla'ul Anwar Banten, 2022)
This study aims to analyze the contents of the novel alive heaven with you by Asma Nadia. The author in this study, wants to analyze the religious values and character education values in the novel alive heaven with you by Asma Nadia. Religious values are divided into several aspects, namely 1) Human relationship with God, 2) Human relationship with oneself 3) Human relationship with other humans 4) Human relationship with the environment. In addition to religious aspects, there are aspects regarding the value of character education, namely 1) Attitudes and behavior in relation to God, 2) Attitudes and behavior in relation to oneself, 3) Attitudes and behavior in relation to family, 4) Attitudes and behavior in relation to society and the nation, 5) Attitudes and behavior in relation to the natural surroundings. The method used in this study is a qualitative method, which is a method that describes and analyzes each part of the content in relation to the religious values in the novel and describes the value of character education in the novel so that the author can find and know the religious value and the value of character education in the novel as long as life is with you. by Asma Nadia. The author chose this method because this method is suitable for use as a way to analyze the religious values and character education values contained in the novel alive heaven with you by Asma Nadia, so that the analysis of the novel is easier and the author can present the results of the analysis carefully, carefully and in detail.